2022
DOI: 10.5829/ije.2022.35.10a.04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Prediction of Self-healing Assessments for AA2014 Based Hybrid Smart Composite Structures: A Novel Fuzzy Logic Approach

Abstract: An idea to heal the damaged surface through healing agents in metallic composite are at their developmental stage. Therefore, the selection of design parameters for a new generation smart composite is more complex and difficult. In the present study the two case studies on self healing smart strucures are included with different input design parameters to evaluate the healing properties. Taguchi based L-8 experiments were conducted to analyze the influencial parameters responsible for higher self healing asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The researchers reported a 100% recovery in crack width, 96.95% recovery in crack depth, and 73.76% recovery in flexural strength. Another study [73,108] on the same hybrid SHMMC demonstrated a 100% recovery in crack width, 87.85% recovery in crack depth, and 75.40% recovery in flexural strength. The studies involved the utilization of a highly sensitive eddy current test at various frequencies to measure the crack depth in SHMMCs.…”
Section: Healing Assessment Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The researchers reported a 100% recovery in crack width, 96.95% recovery in crack depth, and 73.76% recovery in flexural strength. Another study [73,108] on the same hybrid SHMMC demonstrated a 100% recovery in crack width, 87.85% recovery in crack depth, and 75.40% recovery in flexural strength. The studies involved the utilization of a highly sensitive eddy current test at various frequencies to measure the crack depth in SHMMCs.…”
Section: Healing Assessment Resultsmentioning
confidence: 90%
“…AA2014 (an aluminum alloy consisting of Al-Cu-Si-Mn-Mg-Fe) [72,73] The influence of design factors such as SMA volume fraction, pre-strain of SMA wires, and healing temperature on the healing of SHMMCs has not been thoroughly investigated. Poormir et al [51,70] and Srivastava et al [72] conducted experimental studies using the Taguchi method [74] to investigate the impact of design factors, including volume fraction, diameter and pre-strain of SMA, specimen size, and healing temperature, on the healing process of SMA-reinforced SHMMCs.…”
Section: Classification Of Self-healing Metal Matrix Compositesmentioning
confidence: 99%
See 1 more Smart Citation